2023
DOI: 10.1101/2023.04.20.23288852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic performance of plasma Aβ1-42, Aβ1-40and pTau181in the LUMIPULSE automated platform for the detection of Alzheimer disease

Abstract: BACKGROUND: Recently-developed blood markers for Alzheimer's (AD) detection have high accuracy but usually require ultra-sensitive analytic tools not commonly available in clinical laboratories. METHODS: We analyzed plasma samples from 367 consecutive participants in the SPIN cohort, comprising 302 euploid participants (67 cognitively unimpaired, 136 participants with mild cognitive impairment, and 99 with dementia) and 65 with Down Syndrome (46 non-demented and 19 with AD dementia). Participants were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“… 18 A recent report on the Lumipulse Aβ42/40 immunoassay reported an AUC of 0.86 when using abnormal/normal CSF biomarker results as the outcome measure. 24 In agreement with prior reports, the accuracy for detecting amyloid pathology for the Simoa assay was the lowest in our study cohort (AUC of 0.57). Previous studies have reported AUCs for the Simoa assay ranging from 0.62 to 0.78; with a weighted average AUC of 0.69 across 10 cohorts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 18 A recent report on the Lumipulse Aβ42/40 immunoassay reported an AUC of 0.86 when using abnormal/normal CSF biomarker results as the outcome measure. 24 In agreement with prior reports, the accuracy for detecting amyloid pathology for the Simoa assay was the lowest in our study cohort (AUC of 0.57). Previous studies have reported AUCs for the Simoa assay ranging from 0.62 to 0.78; with a weighted average AUC of 0.69 across 10 cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…reported a plasma AUC of 0.91 to distinguish individuals exhibiting both amyloid and tau pathology from amyloid and tau negative individuals compared to CSF biomarkers. 24 …”
Section: Discussionmentioning
confidence: 99%
“…For Lumipulse p-tau217, only one preliminary study suggested a high discrimination accuracy for AD diagnosis, thought without a head-to-head comparison available to date. 20 Despite the growing number of unpublished data available, there is an urgent need for high quality technical and clinical validation of newly developed p-tau217 markers.…”
Section: Introductionmentioning
confidence: 99%